2010
DOI: 10.1007/s12016-010-8227-x
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity in Atopic Dermatitis

Abstract: Atopic dermatitis (AD) is a clinically defined, highly pruritic, chronic inflammatory skin disease. In AD patients, the combination of a genetic predisposition for skin barrier dysfunction and dysfunctional innate and adaptive immune responses leads to a higher frequency of bacterial and viral skin infections. The innate immune system quickly mobilizes an unspecific, standardized first-line defense against different pathogens. Defects in this system lead to barrier dysfunction which results in increased protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 94 publications
3
50
0
6
Order By: Relevance
“…As signal transduction by JAK1 involves multiple downstream signaling pathways (42), it is conceivable that the 2 JAK1 mutations, S645P and R878H, promote JAK1 gain of function, but with variably enhanced activation of different downstream signaling pathways. In fact, it has been reported that point mutations such as mice delayed the onset of disease, suggesting the possible importance of some components of the innate immune response in the initiation of dermatitis (38).…”
Section: Discussionmentioning
confidence: 99%
“…As signal transduction by JAK1 involves multiple downstream signaling pathways (42), it is conceivable that the 2 JAK1 mutations, S645P and R878H, promote JAK1 gain of function, but with variably enhanced activation of different downstream signaling pathways. In fact, it has been reported that point mutations such as mice delayed the onset of disease, suggesting the possible importance of some components of the innate immune response in the initiation of dermatitis (38).…”
Section: Discussionmentioning
confidence: 99%
“…Die Beeinträchtigung der Funktion des Stratum corneum (Hauttrockenheit, erhöh-ter pH-Wert) begünstigt die fast obligatorische Kolonisation läsionaler und nichtläsionaler Haut mit mikrobiellen Erregern, insbesondere mit S. aureus. In den letzten Jahren konnte gezeigt werden, dass Patienten mit atopischem Ekzem deutlich geringere Mengen von antimikrobiellen Peptiden in der Epidermis bilden (β-Defensin-2, -3, das Cathelecidin LL-37 und Dermcidin, [34] …”
Section: Impetiginisiertes Atopisches Ekzemunclassified
“…Einzelne Autoren sprechen bei letzteren Patienten von einer "atopic eruption of pregnancy", wobei sich die -durchaus vielgestaltige -Einzelmorphe nicht wesentlich vom breiten Manifestationsspektrum eines normalen AE abhebt [1]. Die Abgrenzung dieser Ekzemmanifestation vom normalen AE als eigenständige Schwangerschaftsdermatose wird daher von uns und anderen nicht nachvollzogen [11,12].…”
Section: Atopisches Ekzem In Der Schwangerschaftunclassified